Relationship between civil construction and economic growth in Bolivia in the period 1990-2019 - Rocha, Joaquin Humberto Aquino (2026)
This article aims to analyze the relationship between the civil construction sector and its results in the economic growth indicators of Bolivia, in order to determine the impact that this sector has on the economic development of Bolivia. The methodology consisted in the compilation of economic information for the last 30 years (1990-2019), on the relationship of civil construction with the Gross Domestic Product (GDP); variation of the GDP growth rate; Gross Fixed Capital Formation (GFCF); public investment in the infrastructure sector and employment generated. The results show that there are direct and significant relationships between construction and various economic indicators in Bolivia, reflecting the importance of this industry in national economic growth. The provision of economic policies is necessary for sustained growth in this sector.